2009
DOI: 10.1134/s1063778809120126
|View full text |Cite
|
Sign up to set email alerts
|

Neutrino electromagnetic properties

Abstract: The main goal of the paper is to give a short review on neutrino electromagnetic properties. In the introductory part of the paper a summary on what we really know about neutrinos is given: we discuss the basics of neutrino mass and mixing as well as the phenomenology of neutrino oscillations. This is important for the following discussion on neutrino electromagnetic properties that starts with a derivation of the neutrino electromagnetic vertex function in the most general form, that follows from the requirem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
173
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(179 citation statements)
references
References 164 publications
(229 reference statements)
5
173
1
Order By: Relevance
“…[23,24], and a complete review on the neutrino electromagnetic properties can be found in Ref. [25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[23,24], and a complete review on the neutrino electromagnetic properties can be found in Ref. [25].…”
Section: Resultsmentioning
confidence: 99%
“…Nonvanishing θ 13 and the magnetic moment between mass families μ 23 We currently cannot assume a vanishing θ 13 , which was measured with a relatively large value [3][4][5]. Thus, we cannot decouple the system as in Ref.…”
Section: Conversion Probabilitiesmentioning
confidence: 99%
“…All relevant references can be found in Ref. [4] and in the recent review [11]. A more general interpretation of the experimental results which we adopt here is that they are limits on cer- tain nonstandard contributions to neutrino scattering.…”
Section: Weak Mixing Angle and Effective Electron Neutrino Charge Radiusmentioning
confidence: 86%
“…[The literature on neutrino magnetic moments is extensive. For some recent works see [11,12,13] and for recent reviews see [14,15,16]]. In any case one finds that all of the limits above whether experimental or theory are several orders of magnitude larger than the estimate of Eq.…”
Section: Introductionmentioning
confidence: 89%